Lengths of Stay and Discharge Dispositions after Total Knee Arthroplasty: A Comparison of Robotic-Assisted and Manual Techniques - Archer, Allison; Salem, Hytham S.; Coppolecchia, Andrea; Mont, Michael A. (The Journal of Knee Surgery, 2021)
As evidence signifies that short-stay total knee arthroplasties (TKA) can be safe options, it is important to identify factors that contribute to early discharge. There is evidence that robotic-assisted TKAs may lead to shorter lengths of postoperative stays. However, this has not been evaluated as the primary outcome of interest in a large-scale population. The purpose of this study was to compare manual and robotic-assisted TKAs with regard to: (1) length of stay (LOS) and (2) discharge dispositions. TKAs performed between January 1, 2018, to March 31, 2019, were identified. After applying inclusion and exclusion criteria, a total of 10,296 patients were included: 5,993 in the manual and 4,303 in the robotic-assisted group. Length of stay, discharge dispositions, and Charlson comorbidity indices (CCIs) were recorded for all patients. The mean LOS was significantly lower in robotic-assisted (1.68 ± 0.86 days) compared with manual (1.86 ± 0.94 days) TKA procedures (p < 0.00001). In the robotic-assisted group, 2,049 (47.6%) were discharged in 1 day or less compared with 2,325 (38.8%) in the manual group (p < 0.0001). The proportion discharged home was significantly higher for patients who underwent robotic-assisted (91.3%) compared with manual (87.4%) TKAs (p < 0.00001). When comparing only patients who were discharged home and who did not have home health services, the rate was 51.8% in the robotic-assisted group compared with 44.0% in the manual group (p < 0.00001). The mean CCI was similar for patients who underwent robotic-assisted (2.9 ± 1.4 points) compared with manual (3.0 ± 1.5 points) TKAs. There was a trend toward shorter mean LOS for robotic-assisted versus manual TKA at 17 of the 24 included hospital sites (70.8%). Compared with manual, robotic-assisted TKAs demonstrated shorter lengths of postoperative stays and less need for skilled care after discharge. These results suggest the health care burden resulting from an upsurge of TKA procedures in our aging population might be addressed in part by increased utilization of robotic assistance.
Keywords: total knee arthroplasty; length of stay; discharge dispositions; robotic-assisted